Effects and Tolerance of Protein and Energy‐Enriched Formula in Infants Following Congenital Heart Surgery: A Randomized Controlled Trial. Issue 1 (3rd November 2017) - Cui, Yanqin; Li, Lijuan; Hu, Chunmei; Shi, Hui; Li, Jianbin; Gupta, Ramit Kumar; Liang, Huiying; Chen, Xinxin; Gong, Sitang
Abstract: Background: Nutrition support is important for clinical management to improve outcomes of infants following congenital heart surgery. Protein‐enriched and energy‐enriched formula (PE‐formula) may help provide adequate nutrition and promote wound healing. However, the effects and tolerance of increased protein and energy intakes of these infants have not been well defined. Objective: To evaluate nutrition effects and tolerance of a PE‐formula compared with the standard formula (S‐formula) in infants in the first 5 days after congenital heart surgery. Methods : Fifty infants were randomly assigned to S‐formula (S‐group, n = 24) or PE‐formula (PE‐group, n = 26). Daily nutrient intakes and tolerance were recorded. Plasma amino acid concentrations were measured. Cumulative energy balance and nitrogen balance were calculated. Results: Nutrient intakes were significantly higher in the PE‐group after day 1, and all met the adequate intakes as early as day 2. Nitrogen balance in the PE‐group met positive balance from day 2, whereas in the S‐group, this was not until day 5. The PE‐group also had a significantly higher increase in many essential amino acids. With the exception of tolerable diarrhea (multivariate adjusted hazard ratio, 3.16; 95% confidence interval, 1.24–8.01), the PE‐group did not have a significantly higher incidence of intolerable events. Conclusions: In infants during the early postoperative period after congenital heart surgery, early administration of PE‐formula was as well tolerated as S‐formula and effective in achieving higher nutrition intakes and earlier nitrogen balance. Further research is warranted to support the use of PE‐formula in this special group of infants.